Unemployment as a determinant of local service-oriented entrepreneurship: a case study of Poland - Wosiek, Małgorzata (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Unemployment is an important entrepreneurship determinant which is captured by the unemployment push/pull hypotheses. Those issues remain underexplored, with only few studies investigating the relationship between unemployment and the sector structure of entrepreneurship, while considering the specificity of the local economy. Aim: The main goal of the study is to assess the impact of local unemployment rate on the number of newly registered service businesses in Poland, taking into account both the heterogeneity of that sector and the specificities of local economies in 2003–2018. Results: The research results show that in Poland growing unemployment contributed to the increasing registration of new service businesses, which empirically supports the unemployment-push hypothesis. Both the occurrence and the intensity of the unemployment-push effect were conditioned by territorial factors, with the higher elasticity of entrepreneurship in relation to unemployment changes in lagged local units.